2005
DOI: 10.1002/chin.200603004
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Physical and Chemical Properties of Cu in Ce1‐xCuxO2 Oxides.

Abstract: Oxides. -Structural and electronic properties of nanoparticles of the title solid solutions prepared by a reverse microemulsion method are characterized by XRD, XAFS, Raman spectroscopy, and DFT calculations. The Cu atoms embedded in ceria have an oxidation state higher than those of the cations in Cu2O or CuO. The lattices of the title systems still adopt a fluorite-type structure but are highly distorted. The doping of CeO 2 with Cu introduces a large strain into the oxide lattice and favors the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 1 publication
10
53
0
Order By: Relevance
“…5-8 nm nanocrystals [46,47]) onto which copper oxide entities have been dispersed. The chemical state of copper has been shown to be similar for all samples and, in turn, similar to that observed for a CuO reference, with small differences being attributed to interactions with the ceria-related support [18,37], as evidenced by XANES (Figure 1). The existence of a fully oxidized state, Cu(II), of copper in the initial calcined catalysts is also in agreement with XPS investigation, as shown in Figure 2.…”
Section: Redox and Catalytic Properties As A Function Of Changes In Tsupporting
confidence: 68%
See 4 more Smart Citations
“…5-8 nm nanocrystals [46,47]) onto which copper oxide entities have been dispersed. The chemical state of copper has been shown to be similar for all samples and, in turn, similar to that observed for a CuO reference, with small differences being attributed to interactions with the ceria-related support [18,37], as evidenced by XANES (Figure 1). The existence of a fully oxidized state, Cu(II), of copper in the initial calcined catalysts is also in agreement with XPS investigation, as shown in Figure 2.…”
Section: Redox and Catalytic Properties As A Function Of Changes In Tsupporting
confidence: 68%
“…In contrast, the surface area appreciably increases with the copper amount for the samples prepared by microemulsion-coprecipitation, in correlation with the aforementioned introduction of copper into the ceria lattice, which basically induces a decrease in primary particle size (Table 1). On the other hand, concerning the electronic state of copper, XANES (as also shown below) and XPS analyses revealed that the starting sample calcined under dilute O 2 at 500 °C presents copper in a fully oxidized Cu 2+ chemical state with relatively few differences (except for the crystalline CuO detected in 5CuO/CeO 2 ) between the samples concerning copper electronic characteristics [37,40].…”
Section: Nature Of Active Sites/entities and Further Hints On Catalytmentioning
confidence: 84%
See 3 more Smart Citations